Rapid assessment of disability in the Philippines: understanding prevalence, well-being, and access to the community for people with disabilities to inform the W-DARE project. Issue 1 (December 2016) - Marella, Manjula; Devine, Alexandra; Armecin, Graeme; Zayas, Jerome; Marco, Ma; Vaughan, Cathy
Abstract Background International recognition that people with disabilities were excluded from the Millennium Development Goals has led to better inclusion of people with disabilities in the recently agreed Global Goals for Sustainable Development (SDGs) 2015–2030. Given the current global agenda for disability inclusion, it is crucial to increase the understanding of the situation of people with disabilities in the Philippines. The aim of this study was to estimate the prevalence of disability and compare the well-being and access to the community between people with and without disabilities. Methods A population-based survey was undertaken in District 2 of Quezon City and in Ligao City. 60 clusters of 50 people aged 18 years and older were selected with probability proportion to size sampling from both locations. The Rapid Assessment of Disability (RAD) survey was used to identify people with disabilities based on their responses to activity limitations. The levels of well-being and access to the community for people with disabilities were compared with controls matched by age, gender, and cluster. Information on barriers to accessing the community was also collected. Results The prevalence of disability was 6.8 (95 % CI: 5.9, 7.9) and 13.6 % (95 % CI: 11.4, 16.2) in Quezon City and Ligao City respectively. Psychological distress was the most commonly reported condition in both locations, although it was often reported with a co-morbid condition related to sensory, physical, cognitive, and communication difficulties. The prevalence of disability was associated with age and no schooling, but not associated with poverty. People with disabilities had significantly lower well-being scores and reduced access to health services, work, rehabilitation, education, government social welfare, and disaster management than people without disability. Having a disability and negative family attitudes were reported as barriers for people with disabilities participating in work, community meetings, religious activities, and social activities. Conclusions The prevalence of disability among adults in District 2 of Quezon City and in Ligao City is higher than the estimated national prevalence of disability derived from the 2010 Philippines census. Disability is also associated with lower well-being and reduced participation across a number of domains of community life.